Microbially-Mediated Transformations of Estuarine Dissolved Organic Matter - Medeiros, Patricia M.; Seidel, Michael; Gifford, Scott M.; Ballantyne, Ford; Dittmar, Thorsten; Whitman, William B.; Moran, Mary Ann (Frontiers in Marine Science, 2017)
Microbially-mediated transformations of dissolved organic matter (DOM) in a marsh-dominated estuarine system were investigated at the molecular level using ultrahigh resolution mass spectrometry. In addition to observing spatial and temporal variability in DOM sources in the estuary, multiple incubations with endogenous microorganisms identified the influence of DOM composition on biodegradation. A clear microbial preference for degradation of compounds associated with marine DOM relative to those of terrestrial origin was observed, resulting in an overall shift of the remaining DOM toward a stronger terrigenous signature. During short, one-day long incubations of samples rich in marine DOM, the molecular formulae that were enriched had slightly smaller mass (20-30 Da) and number of carbon atoms compared to the molecular formulae that were depleted. Over longer time scales (70 days), the mean differences in molecular mass between formulae that were depleted and enriched were substantially larger (~270 Da). The differences in elemental composition over daily time scales were consistent with transformations in functional groups; over longer time scales, the differences in elemental composition may be related to progressive transformations of functional groups of intermediate products and/or other reactions. Our results infused new data toward the understanding of DOM processing by bacterioplankton in estuarine systems.